Biochemical and biophysical cues of the extracellular matrix modulates stem cell fate: Progress and prospect in extracellular matrix mimicking biomaterials - Anuska Mishra; Unnati Modi; Rahul Sharma; Dhiraj Bhatia; Raghu Solanki (Biomedical Engineering Advances)
Stem cell therapies hold immense promise for the treatment of a wide range of diseases; however, the full therapeutic potential remains untaped. This limitation arises primarily from our incomplete understanding of the complex mechanisms of stem cell niches. A promising avenue of research lies in the development of Extracellular Matrix (ECM)-based novel biomaterials, which closely mimic the natural microenvironment of stem cells. These biomaterials provide essential biophysical and biochemical cues necessary for mechanotransduction, thereby enhancing the efficacy and safety of stem cell therapies by precisely modulating stem cell fate. In this review, we discuss the critical role of the stem cell niche and its interplay with ECM, detailing its structural composition and functional significance. We further explore how the biophysical and biochemical factors of the ECM modulate specific transmembrane receptors, triggering intracellular signaling mechanisms that regulate cell morphology, cytoskeletal dynamics, viability, migration, and differentiation. Engineered biomaterials to replicate the properties of the ECM are discussed along with the incorporation of tailored biophysical and biochemical cues into scaffolds and biomaterials to modulate stem cell fate. Overall, this review underscores the innovative applications of ECM mimicking biomaterials in biomedical engineering, emphasizing their transformative potential to modulate stem cell fate and advance regenerative medicine.